2018
DOI: 10.4103/heartviews.heartviews_82_16
|View full text |Cite
|
Sign up to set email alerts
|

Procedure time comparison between radial versus femoral access in ST-segment elevation acute myocardial infarction patients undergoing emergent percutaneous coronary intervention: A Meta-analysis of controlled randomized trials

Abstract: Introduction:There are inconclusive data about the potential delay of procedure time in emergent percutaneous coronary intervention (PCI) by radial compared with femoral approach in patients with ST-segment elevation myocardial infarction (STEMI).Aims:The purpose of the current study is to conduct a comprehensive meta-analysis of controlled randomized trials (CRTs) comparing the procedure time in STEMI patients undergoing emergent PCI with radial versus femoral access.Methods:Formal search of CRTs through elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Coronary artery intervention technology belongs to the category of vascular recanalization and is the least traumatic method of myocardial blood flow reconstruction. [11] Previous studies have shown that renal insufficiency increases the poor prognosis of cardiovascular diseases. [12] Recent reports have shown that renal impairment is common in patients with acute coronary syndrome and is associated with a high risk of death, even when perfusing with the most effective method, such as PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery intervention technology belongs to the category of vascular recanalization and is the least traumatic method of myocardial blood flow reconstruction. [11] Previous studies have shown that renal insufficiency increases the poor prognosis of cardiovascular diseases. [12] Recent reports have shown that renal impairment is common in patients with acute coronary syndrome and is associated with a high risk of death, even when perfusing with the most effective method, such as PCI.…”
Section: Introductionmentioning
confidence: 99%